BOLD fMRI A Guide to Functional Imaging for Neuroscientists - Faro, Scott H.; Mohamed, Feroze B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
BOLD fMRI: A Guide for Neuroscientists is a compilation of key chapters selected by the editors to present neuroscientists with a comprehensive introduction to the basic principles of BOLD fMRI and its applications in cognitive neuroscience. This comprehensive book introduces important topics in BOLD fMRI such as scanning methodologies, experimental design and data analysis, and its challenges and limitations. Clinical applications of functional imaging are included in chapters on brain mapping in cognitive neuroscience, memory in aging and dementia, language systems, and the Wada test. Also included is a full-color neuroanatomical atlas of the basic motor, sensory, and cognitive activation sites that are discussed throughout the book. With contributions from internationally recognized neuroradiologists, neurologists, psychiatrists, cognitive neuroscientists, and physicists, this volume will appeal to all neuroscientists seeking a concise introduction to the fundamentals of BOLD fMRI.
BOLD Functional MRI -- Principles of Functional MRI -- fMRI Scanning Methodologies -- Experimental Design and Data Analysis for fMRI -- Challenges in fMRI and Its Limitations -- Clinical Challenges of fMRI -- fMRI Clinical Applications -- Brain Mapping for Neurosurgery and Cognitive Neuroscience -- fMRI of Memory in Aging and Dementia -- fMRI of Language Systems: Methods and Applications -- fMRI Wada Test: Prospects for Presurgical Mapping of Language and Memory -- Cognitive Neuroscience Applications -- Neuroanatomical Atlas -- Neuroanatomical Atlas.
Keywords: Medicine; Radiology, Medical; Neurology; Psychiatry; Medicine & Public Health; Imaging / Radiology; Neuroradiology; Diagnostic Radiology; Neurology; Psychiatry